From Likes to Loyal: An Analysis of the Influence of Social Media, Trust Levels, and Communication Mediated by Customer Bonding on Loyalty at CV. Rumah Lamongan - Ernaningsih, Anisah; Handayani , Wiwik; Bachtiar , Arief (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study to purpose for examines the influence of social media, trust level, and communication on customer loyalty with customer bonding as a mediating variable. Social media enhances effective communication and trust between the company and its customers, thereby strengthening customer loyalty. Customer bonding reinforces the emotional connection between customers and the company, which in turn increases loyalty. The results indicate that social media, trust, and communication have a positive and significant impact on customer loyalty through customer bonding at CV. Rumah Lamongan. This research is included in the type of quantitative research with a correlational design. The research method used was primary data collection through a questionnaire in the form of a Google Form. The research findings conclude that: (1) Social Media positively contributes to loyalty, (2) The level of trust positively contributes to loyalty, (3) Communication does not positively contribute to loyalty, (4) Social Media contributes to loyalty through customer bonding, (5) The level of trust contributes to loyalty through customer bonding, (6) Communication contributes to loyalty through customer bonding.